2015
DOI: 10.1520/jte20130285
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Test Technique to Evaluate “Self-Sealing” of Concrete

Abstract: Concrete is prone to cracking when subjected to tensile forces because of its low tensile strength. The cracking potential is an even bigger concern when concrete is relatively young and is in the plastic stage. Cracks induced early can grow with time because of drying shrinkage and with application of service loads. Concrete, which is otherwise impermeable, allows for free passage of moisture and other deleterious chemicals when it is cracked, leading to reduced durability of the material and, in many cases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…Although the average crack width for both specimens is very similar but the initial flow rate is higher for CWA specimens. This confirms that equivalent crack sizes of CWA samples, proposed in [ 32 ], are greater than control mixes while their actual crack width is the same. In other words, two samples with the same surface crack width do not necessarily have the same water flow rate.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Although the average crack width for both specimens is very similar but the initial flow rate is higher for CWA specimens. This confirms that equivalent crack sizes of CWA samples, proposed in [ 32 ], are greater than control mixes while their actual crack width is the same. In other words, two samples with the same surface crack width do not necessarily have the same water flow rate.…”
Section: Resultssupporting
confidence: 81%
“…According to the Robertson study et al, the concrete panels containing similar hydrophilic CWA as the one in this work, performed well, showing low half-cell values and no apparent evidence of corrosion after 10 years of exposure in a real-field corrosive environment [ 31 ]. Authors also performed various testing and evaluated different durability properties of CWA concrete [ 13 , 14 , 15 , 18 , 32 , 33 ]. The authors’ findings of assessing the permeability and self-sealing of CWA concrete with two different common cement types revealed that adding CWA to the concrete mix reduced the water permeability coefficient by three times while increasing the self-sealing ratio at a faster rate [ 13 , 14 , 18 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, authors are also studying the effect of selfsealing on resistivity of concrete. Previous work done in this area (self-sealing) is reported elsewhere [114,115].…”
Section: Correlation Between Electrical Resistivity and Reinforcementmentioning
confidence: 99%
“…There was no possibility of a visual analysis of the cracks and their sealing, since the specimens would be compromised, and the readings of the ultrasound pulse velocity would not be continued. Therefore, the authors recommend future studies containing ultrasonic test and image analysis in parallel, with more specimens and using a cracking method that would allow standardization and identification of the exact location of the cracks, such as those applied by Gupta and Biparva [27] and El-Newihy et al [28]. and drying cycle, again being related to the availability of anhydrate particles in the early ages.…”
Section: Effect Of Cracking Induction Age On Concrete Self-healingmentioning
confidence: 99%